Geoelectric Methods to Determine the Location of Old Graves - Aco Wahyudi Efendi (Indonesian Scientific Journal, 2022)
Gunung Selendang site is known for being classified as a burial site containing human bones, based on excavation findings in the form of a jug tomb (tajau), including; Limbs, hip fragments, jaw fragments, teeth, skull fragments, and small bone fragments that are difficult to identify. In general, the Tajau shape at this point consists of two groups, namely the slender Tajau group with wavy lips with a diameter of 23.5 cm and the chubby Tajau group with simple, unadorned lips with a diameter of 22 cm. Geophysical methods widely used in exploration include seismic, magnetic, gravitational, electrical, and electromagnetic resistance methods. The geoelectric method is one of the geophysical exploration methods that can be used to study the properties of a geothermal system, determine the lithology of rock layers, deposit locations, flow patterns, and the distribution of geothermal fluids below the earth's surface.From this material it can be clearly seen in the color of the soil layer and shows a collection of urn-shaped material in this color at a depth of up to 2 meters and according to the knowledge that from the side of the soil to a depth of 2 meters a collection of Urns with ancient fragments found.